Synthesis and electrochemical properties of rGO/polypyrrole/ferrites nanocomposites obtained via a hydrothermal route for hybrid aqueous supercapacitors - Mariappan, Chinnasamy Ramaraj; Gajraj, V; Gade, S; Kumar, A; Dsoke, S; Indris, Sylvio; Ehrenberg, Helmut; Vijaya Prakash, Gaddam; Rajan, Jose (Elsevier, 2019)
In this work, ternary hybrid nanocomposites with different weight percentages of rGO/Ppy/CoFe2O4 and rGO/Ppy/Fe3O4 were synthesized through a hydrothermal approach. Structural properties were investigated by using Fourier transform infrared spectroscopy, Raman spectroscopy, X-ray diffraction, and transmission electron microscopy (TEM) with selected area electron diffraction. TEM studies show embedded spinel-type metal oxide nanoparticles, branched Ppy chains and Ppy particles on rGO. The results of the structural and morphological investigations clearly reveal the formation of ternary hybrid nanocomposites. The influence of the content of spinel-type metal oxides on electrochemical properties of nanocomposites was investigated via cyclic-voltammetry, electrochemical impedance spectroscopy and galvanostatic charging/discharging measurements in 1 M LiNO3 electrolyte. The specific capacitance is found to be 261, 141, 108 and 68.3 F g−1 at 1 A g−1 for 37wt%rGO/58Ppy/5Fe3O4 (FO5), 32wt%rGO/54Ppy/14Fe3O4 (FO14), 37wt%rGO/58PPy/5CoFe2O4 (CFO5), and 32wt%rGO/54Ppy/14CoFe2O4 (CFO14), respectively. Charge storage mechanisms were interpreted through Power's law and Trasatti plot. Among these samples, FO5 exhibits high specific capacitance with good rate capacitance performance (163 F g−1 at 10 A g−1). A hybrid supercapacitor was fabricated with FO5 composite as a positive electrode, activated carbon (AC) as a negative electrode and 1 M LiNO3 as an electrolyte. As a result, the FO5//AC cell exhibits the specific capacitance of 31.8 F g−1 at 3.0 A g−1 with excellent rate capability and good cycling performances. The energy and powder densities are found to be in the range of 17.74–4.17 Wh kg−1 and 0.3–10.4 kW kg−1 respectively with an output voltage of 0–1.6 V.